Variação interanual de indicadores hidroclimáticos na bacia do Alto Rio Paraguai, Brasil. - Bastos, Yandra Fontes (2014)
The change of land use causes changes in the hydrological cycle of drainage basins and consequently in river channels and the habitats of aquatic organisms. The main changes of the hydrological cycle relate to the amount of water available for runoff that is adequately represented by humidity index (UI) and how the basin ecosystem uses this water that the Horton index (HI) estimates. In rivers channels the Indicators of Hydrologic Alteration (IHA) allow to track any changes to hydrological regime while the Froude number (Fr) is an indicator of the hydraulic characteristics of flow in the channel. The substitution of natural vegetation by pastureland and crops already occurs in about half the area of the Upper Paraguay River Basin (BAP) and already constitutes a real possibility of modifying the hydrological cycle of that basin. Thus, the goal of this work is to evaluate the influence of landscape characteristics and climate as represented by humidity and Horton indexes on the physical characteristics of river habitat in the channel as represented by Fr and IHA in the northern portion of BAP. The hydro-climatic parameters used in the calculation of the indicators were obtained from the database of the National Water Agency. Data from 17 rainfall and fluvial stations were selected. In those 17 seasons the polygons of sub-watersheds were delimited based on digital elevation model and subsequently adjusted to regionalized rainfall for each sub-basin based on available isohyet maps. To investigate whether the processes that occur at the basin scale (represented by IH and IU) are influencing the processes that occur on the scale of fluvial channels (represented by Fr and IHA), a Pearson correlation analysis was carried. As IHA produces a series of indicators, a principal component analysis was performed to reduce this complexity and extract the most significant variable, which was the minimum flow rate of 90 days (90daysMin). The average value of IH was 0.76 (ranging from 0.50 to 0.93) is similar to values found in the literature and correlates significantly (p <0.05) with 90daysMin and Fr. The average UI is 0.85 (ranging from 0.55 to 1.30) and does not correlate significantly with indicators of physical habitat in the channels. The range of the humidity index characterizes the climate of the BAP mostly as humid (> 0.65) and somewhat less in the dry sub-humid class. The small variation of UI when compared to study in temperate-humid climate in North America (0.2 to 5.0), possibly explains why no significant correlations between UI and 90daysMin and Fr were observed. A correlation analysis was also performed for each of the sub-basins, as well as a trend analysis by sub-basin to evaluate how the indexes varied over time. The 90daysMin and Fr are most often correlated significantly with time than IH and IU. In general, 90daysMin diminished with time, except in one sub-basin and this is attributed to increased soil compaction with consequent reduction in base flow. In 5 sub-basins, Fr increased over time while it decreased in two others. This maybe due to land use change provoking degradation of riparian areas and channel erosion (decreasing Fr) with subsequent siltation downriver (increasing Fr).In general, the channel indexes, Fr and 90daysMin, seem to reflect the historical use and occupation of BAP better than indicators of watershed processes (IU and IH), which practically do not correlate with time.